Waveform characteristics in thoracic paravertebral space: a prospective observational study [version 2; peer review: 2 approved] - Pattika Subsoontorn; Lalinthip Vareesunthorn; Amorn Vijitpavan; Sivaporn Termpornlert (F1000Research)
Background With increased use of thoracic paravertebral block (TPVB) in thoracic surgery, many faced the challenge of locating the thoracic paravertebral space (TPVS) ultrasonographically. This observational study aimed to investigate the waveform characteristics and pressure value within the TPVS in anaesthetized patients with controlled ventilation. Methods 50 patients scheduled for elective lung surgery were enrolled. After conduction of anesthesia, all patients underwent TPVB at T4/5 and T6/7 using transverse, in-plane ultrasound guidance. A pressure transducer system with a desktop monitor was connected to the needle hub to measure pressure values and waveform characteristics in three locations: the paraspinal muscles, immediately behind the superior costotransverse ligament, and within the TPVS. Next, 15 mL of 0.33% bupivacaine was injected into each desired TPVS. After completion of the surgery, the extent of dermatomal blockade and the pain score was assessed in all patients. Results 98 typical regular respiratory waveforms with a mean pressure of ≤ 25 mmHg were detected in the TPVS of 50 patients. The sensitivity of the combined ultrasound and pressure waveform measurement technique to identify the TPVS was 95.45% (95% confidence interval, 84.527–99.445). Nontypical respiratory waveforms were present in two patients. Factors interfering with the TPVS waveform characteristics were previous thoracic surgery. Conclusion The TPVS had low pressure and showed a smooth, regular waveform pattern corresponding to respiration.